Athlete Scandals and Endorsement Marketing: Research Trends and Introduction to Topics. Issue 2 (3rd April 2018) - Kwak, Dae Hee; Lee, Joon Sung; Chan-Olmsted, Sylvia
ABSTRACT: Endorsement marketing has been widely used to generate consumer attention, interest, and purchase behaviors among targeted consumers. However, relatively little systematic research has been conducted to understand what happens to endorsed brands and athletes when an athlete engages in a scandal. This article briefly reviews concepts discussed in the athlete transgression research, and briefly describes the five articles included in this special issue. This article extends a note of appreciation to the members of the support staff and special issue editorial board.